REGIONAL LIVESTOCK QUOTA SYSTEM UNDER ENVIRONMENTAL CAPACITY IN KOREA - 송주호 (한국농촌경제연구원, 2005)
Livestock manure is a good source of nutrient necessary for crop growing. In Korea, however, nutrient supply for crop growth is larger than the nutrients demand in many regions, thus environmental concerns associated with livestock manure are rising. Many policy measures have been implemented but with little effect. Recognizing the urgent need to improve environmental burdens of livestock production, the government announced a new plan to introduce a Nutrient Maximum Loads System in 2007. The concept of this system is to limit the total supply of nutrients according to the nutritional needs of the region. Livestock manure as well as the consumption of chemical fertilizer is accounted for in the calculation of nutrient supply. This is less restrictive than regulating the numbers of livestock since there exists flexibility to choose between chemical fertilizer and livestock when there is a need to reduce nutrient supply. If this system proved to be ineffective, then Regional Livestock Quota System would be introduced in 2011. This study explained the necessity of introducing a target oriented policy tool to prevent environment from deterioration with respect to livestock manure. The experiences from these systems in coming years in Korea would provide useful information for other countries.
Keywords: Livestock Manure; Environment; Maximum loads; Quota; Nutrient; Regulations; Economic Instrument; Density; Livestock Unit; Nitrogen balance; Livestock Manure; Environment; Maximum loads; Quota; Nutrient; Regulations; Economic Instrument; Density; Livestock Unit; Nitrogen balance